2013
DOI: 10.1016/j.cmet.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stress Modulates Alzheimer’s β-Secretase Gene Transcription via SIRT1-PPARγ-PGC-1 in Neurons

Abstract: Summary Classic cardio-metabolic risk factors such as hypertension, stroke, diabetes and hypercholesterolemia all increase the risk of Alzheimer’s disease. We found increased transcription of β-secretase/BACE1, the rate-limiting enzyme for Aβ generation, in eNOS deficient mouse brains and after feeding mice a high fat high cholesterol diet. Up- or down-regulation of PGC-1α reciprocally regulated BACE1 in vitro and in vivo. Modest fasting in mice reduced BACE1 transcription in the brains which was accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(144 citation statements)
references
References 61 publications
5
132
0
Order By: Relevance
“…[8][9][10][11] Alzheimer disease is one of neurodegenerative diseases, but vascular pathology contributes to Alzheimer disease changes to variable degrees. [30][31][32][33][34] There is an emerging concept of protein elimination failure arteriopathy 35 where waste products such as amyloid-β accumulate in the brain as a result of cerebral perfusion failure and evoke disparate brain disorders because perivascular drainage of waste products are driven by arterial pulsation.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Alzheimer disease is one of neurodegenerative diseases, but vascular pathology contributes to Alzheimer disease changes to variable degrees. [30][31][32][33][34] There is an emerging concept of protein elimination failure arteriopathy 35 where waste products such as amyloid-β accumulate in the brain as a result of cerebral perfusion failure and evoke disparate brain disorders because perivascular drainage of waste products are driven by arterial pulsation.…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is widely present in the brain (neurons and microglia), lowers local levels of iNOS (inducible nitric oxide synthase) and COX-2 (cyclooxygenase-2), and might constitute an effective target in the treatment of ischaemia [42]. Moreover, the impact of metabolic stress on SIRT1-PPARγ signalling has been suggested to modulate β-secretase and thus the rate of amyloid β production in AD [211]. Additionally, differential expression of Sirt1 and PPARγ has been noted in Aβ-treated glia, which would fit the above-mentioned antagonistic regulation of Sirt1 by PPARγ; it has been proposed to mediate the neuroprotective reaction of astrocytes elicited by in vitro Aβ treatment [4].…”
Section: Transcriptional and Post-transcriptional Regulators As Sirtumentioning
confidence: 99%
“…There are four potential RAR-PPAR-RXR-responsive elements predicted in BACE1 promoter (7,40). To determine whether the repressive effect of atRA on BACE1 promoter depends on retinoid receptors, we first tested the impact of overexpressed receptors on the co-expressed BACE1-luciferase construct.…”
Section: Atra Treatment Reduces Cortical Bace1 Expression Inmentioning
confidence: 99%
“…We recently reported that that BACE1 transcription is up-regulated by metabolic risk factors and that the key metabolic regulatory pathway of AMPK-SIRT1-PGC-1␣ (where AMPK is AMP-activated protein kinase) suppressed BACE1 transcription by directly acting on the first PPAR-responsive element (PPRE) in the BACE1 gene both in cultured neurons and in vivo settings (calorie restriction, etc.) (6,7). Although the identification of several putative binding sites for NFB and PPAR␥ in BACE1 promoter strongly implicates its regulation under inflammatory condition, compelling evidence is lacking.…”
mentioning
confidence: 99%